2008
DOI: 10.1177/0898264308315426
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Variations in Caregiver Service Use

Abstract: These findings suggest that racial and ethnic disparities in caregiver service use found at the bivariate level are attributable to covarying predisposing, enabling, and need factors. Further research and theoretical development are suggested to clarify the impact of sociocultural factors on caregiver service use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 36 publications
(62 reference statements)
3
59
1
Order By: Relevance
“…In addition, the DfT wanted to focus on possible differences by race and ethnicity. This decision is generally supported by a large body of work that shows racial and ethnic differences in all aspects of caregiving to older family members even holding other variables constant (Laditka and Laditka, 2001;Ramos, 2004;Sarkisian, 2004;Sander et al, 2007;White-Means and Rubin, 2008;Herrera et al, 2008;Scharlach et al, 2008;Brown, 2008), although there are also contrasting views suggesting that racial/ethnic differences disappear after controlling for socio-economic variables (see Ball et al, 2009;Siefert et al, 2008;Brown et al, 2009).…”
Section: The Study Rationalementioning
confidence: 95%
“…In addition, the DfT wanted to focus on possible differences by race and ethnicity. This decision is generally supported by a large body of work that shows racial and ethnic differences in all aspects of caregiving to older family members even holding other variables constant (Laditka and Laditka, 2001;Ramos, 2004;Sarkisian, 2004;Sander et al, 2007;White-Means and Rubin, 2008;Herrera et al, 2008;Scharlach et al, 2008;Brown, 2008), although there are also contrasting views suggesting that racial/ethnic differences disappear after controlling for socio-economic variables (see Ball et al, 2009;Siefert et al, 2008;Brown et al, 2009).…”
Section: The Study Rationalementioning
confidence: 95%
“…These include disparities in formal caregiver support service use (DilworthAnderson et al 2002;Janevic and Connell 2001;Scharlach et al 2008) and the types and sources of support that caregivers received (Chow et al 2010). Some studies have reported that non-Hispanic White caregivers compared to minority counterparts use more formal caregiver services (Dilworth-Anderson et al 2002;Scharlach et al 2006) while other earlier studies reported a higher level of service use by caregivers of color (Cox 1996;Schoenberg et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Another found no association between caregivers' race/ethnicity and their rate of service utilization (Brown et al 2012). Scholars have examined possible factors that might explain racial/ethnic differences in service use, which include cultural norms of and family's expectation toward caregiving (Chow et al 2010;Scharlach et al 2006Scharlach et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…As evident in the literature, these families are frequently underserved and lack access to culturally competent supports across the life course (e.g., Al Khateeb, Al Hadidi, & Al Khatib, 2014;Magaña & Smith, 2008;Scharlach, Giunta, Chow, & Lehning, 2008). Additionally, more research needs to include the impact of cultural beliefs on the practices of family caregiving in cross-cultural and culture-specific research at different life-course stages (see, e.g., Fingerman, VanderDrift, Dotterer, Birditt, & Zarit, 2011;Sage & Jegatheesan, 2010;Sander et al, 2007).…”
Section: Familymentioning
confidence: 99%